Left-hemisphere ischemic stroke as a complication of cutaneous lupus erythematosus - Ślusarz, Krystian; Wierzbicki, Krzysztof; Adamczyk-Sowa, Monika (Journal of Education, Health and Sport, 2019)
We describe the case of a 33-year-old patient with cutaneous lupus erythematosus admitted to the Department of Neurology due to the weakness of right limbs and speech disorders after night sleep. On admission, neurological examination revealed: no verbal contact; mixed aphasia with motor predominance; wide, symmetrical and reactive pupils; conjugate gaze palsy in a horizontal direction; right-sided hemianopsia and right-sided pyramidal tract syndrome with right limbs paralysis and bilaterally positive Babinski's sign. Magnetic resonance imaging revealed changes in the type of fresh ischemia in the left hemisphere of the brain – in the temporal lobe / basal ganglia on the left side hyperintensive areas were visible. As a result of the therapy and rehabilitation, the patient's general and neurological condition was improved. The patient was discharged home with recommendations in good general condition.